Nonlinear Self‐Accelerating Pulses Shedding from Airyprime Pulses in Kerr Media - Xuri Yang; Qi Huang; Yanxia Gao; Dianyuan Fan; Lifu Zhang (Advanced Photonics Research)
Herein, the propagation of truncated Airyprime pulses in nonlinear optical fibers with anomalous or normal dispersion is studied. Nonlinear self‐accelerating pulses generation, which is in sharp contrast to that of Airy pulses, is observed. Accelerating pulses have notable redshifted spectral notch (double peaks) or single blueshifted spectral peak depending on whether the dispersion is anomalous or normal. The emergent nonlinear self‐accelerating pulses are very sensitive to the truncated coefficient. The relationship between the characteristics of such accelerating pulses and the truncated coefficient is disclosed and compared in detail. The results not only shed new light on the nonlinear propagation of Airyprime pulses, but also provide a novel method to generate nonlinear self‐accelerating pulses as well as enable the realization of very efficient wavelength conversion based on the controlled frequency shift. Based on space–time duality, self‐accelerating spatiotemporal nonlinear light bullets can be envisaged from the propagation of spatiotemporal Airyprime wave packets in pure Kerr medium.